Jitter correction for transmission X‐ray microscopy via measurement of geometric moments. (19th August 2019) - Wang, Shengxiang; Liu, Jianhong; Li, Yinghao; Chen, Jian; Guan, Yong; Zhu, Lei
Abstract : An accurate and efficient method for jitter correction in transmission X‐ray microscopy is presented. Abstract : Transmission X‐ray microscopes (TXMs) have become one of the most powerful tools for imaging 3D structures of nano‐scale samples using the computed tomography (CT) principle. As a major error source, sample jitter caused by mechanical instability of the rotation stage produces shifted 2D projections, from which reconstructed images contain severe motion artifacts. In this paper, a jitter correction algorithm is proposed, that has high accuracy and computational efficiency for TXM experiments with or without nano‐particle markers. Geometric moments (GMs) are measured on segmented projections for each angle and fitted to sinusoidal curves in the angular direction. Sample jitter is estimated from the difference between the measured and the fitted GMs for image correction. On a digital phantom, the proposed method removes jitter errors at different noise levels. Physical experiments on chlorella cells show that the proposed GM method achieves better spatial resolution and higher computational efficiency than the re‐projection method, a state‐of‐the‐art algorithm using iterative correction. It even outperforms the approach of manual alignment, the current gold standard, on faithfully maintaining fine structures on the CT images. Our method is practically attractive in that it is computationally efficient and lowers experimental costs in current TXM studies without using expensive nano‐particles markers.